2015
DOI: 10.5897/ijnam2015.0180
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise training has anorexogenic effect associated with improved oxidative stress in obese women

Abstract: Endocrine derangement and oxidative stress are two distinguishing features of obesity that have limited the success rate of various management strategies, especially physical activities. The objective of the current study was to examine the effect of 8 weeks of moderate-intensity regular exercise training on oxidative stress, appetite and weight loss in obese women compared with normal-weight women. Sixteen normal-weight (body mass index (BMI) < 25 kg/m 2 ) and fifteen obese women (BMI > 30 kg/m 2 ) exercised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…In accordance with our results, a negative correlation has been reported between nesfatin-1 and variables such as body fat percentage by a few previous studies (Tsuchiya et al, 2010;Mogharnasi et al, 2019b). In addition, it has been reported that 8 weeks of moderateintensity aerobic exercise diminished BMI and insulin and raised serum levels of nesfatin-1 in obese women (Nabil and El Sayyad, 2015). As noted in the literature, nesfatin-1 is highly sensitive to long-term training and significant loss of weight and fat percentage (Nabil and El Sayyad, 2015;Mogharnasi et al, 2019a).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our results, a negative correlation has been reported between nesfatin-1 and variables such as body fat percentage by a few previous studies (Tsuchiya et al, 2010;Mogharnasi et al, 2019b). In addition, it has been reported that 8 weeks of moderateintensity aerobic exercise diminished BMI and insulin and raised serum levels of nesfatin-1 in obese women (Nabil and El Sayyad, 2015). As noted in the literature, nesfatin-1 is highly sensitive to long-term training and significant loss of weight and fat percentage (Nabil and El Sayyad, 2015;Mogharnasi et al, 2019a).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been reported that 8 weeks of moderateintensity aerobic exercise diminished BMI and insulin and raised serum levels of nesfatin-1 in obese women (Nabil and El Sayyad, 2015). As noted in the literature, nesfatin-1 is highly sensitive to long-term training and significant loss of weight and fat percentage (Nabil and El Sayyad, 2015;Mogharnasi et al, 2019a).…”
Section: Discussionmentioning
confidence: 91%
“…The purpose of conducting this review is to assess the existing research evidence regarding the impact of exercise on Nucleobindin-2 (NUCB2) gene expression and Nesfatin-From the 36 included studies, 23 examined humans with 13 examining animal models. [64][65][66][67][68][69][70][71][72][73][74][75][76] Studies investigated the effects of chronic exercise training [41][42][43][44][45][46][47][48][49][50][51]63 and acute exercise 48,[52][53][54][55][56][57][58][59][60][61][62] in humans.…”
Section: Significance Statementmentioning
confidence: 99%
“…Several studies have investigated the effect of endurance exercise training on Nesfatin-1 concentration in humans. 41,46,48,50,51,63 Ahmadizad et al investigated the effects of 6 weeks of highintensity interval training (HIIT: 3 days per week for 6 weeks) and moderate-intensity continuous exercise training (MICT: 3 days per week for 6 weeks) followed by a week of detraining on plasma Nesfatin-1 of physically inactive overweight men. They showed that plasma Nesfatin-1 only increased as a result of HIIT.…”
Section: Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation